Custom Bus optimization of docking stations based on partition path selection. (October 2017) - Li, Wenyong; Yu, Ziwei; Wei, Shuo; Lu, Xiayun; Zhang, Yuanqing; Wang, Tao
The Custom Bus has advantages on punctuality, direct arrival, and economic benefits. It has a good effect on attracting passengers from private cars commuting in city. Due to the unscientific docking stations, the Custom Bus is always ineffective. There are little studies about the optimization of docking stations. Based on the reference to minimum cost maximum flow problem, using the chain of minimum cost increase flow and the Dijkstra algorithm, choosing points by 0-1 planning model, studying the docking forms on multi-origin to multi-destination. Guaranteeing the attendance rate and limited docking stations, to achieve the goals that shortest single path and the highest service rate by arranging the docking stations reasonably. This algorithm has been demonstrated during the process of optimizing Custom Bus docking stations between Guilin's new and old urban districts.